ENABLING DATA PORTABILITY AND INTEROPERABILITY UNDER INDONESIA'S DATA PROTECTION LAW - Wiwoho, Jamal; Pati, Umi Khaerah; Pratama, Anugrah Muhtarom (Masalah-Masalah Hukum, 2024)
The Indonesian parliament ratified the Personal Data Protection (PDP) Law in October 2022, introducing the Right to Data Portability (RtDP) in Article 13. This concept enables seamless information transfer, enhances personal control, and fosters innovation in the digital economy. This study analyzed data portability provisions under the PDP Law and drew insights from the EU and UK's experiences. Findings showed that data portability under the PDP Law, similar to the GDPR, fell short due to the absence of standardized guidelines, interoperability architectures, and non-mandatory compatibility policies. Prioritizing Open APIs for interoperability was crucial. Effective public-private collaboration was key in establishing sector-specific and cross-sector interoperability standards aligned with PDP Law regulations